THE INFLUENCE OF CLIMATIC CONDITIONS ON THE OCCURRENCE OF LARGE FOREST FIRES: A CASE STUDY OF STARA PLANINA NATURE PARK IN 2007 AND 2019 - Stanimir ŽIVANOVIĆ; Milena GOCIĆ (Journal of Applied Life Sciences and Environment)
This work investigates the relationship between the occurrence of large forest fires (more than 1,000 ha) and meteorological data. Specifically, it analyzes the characteristics of large forest fires in July 2007 (2,500 ha) and October 2019 (2,108 ha) in Serbia’s Stara Planina Nature Park (NP). The results show that at these times, forest fires occurred during long heatwaves with low relative humidity and high air temperature. Dry climatic conditions in the preceding months also contributed to the occurrence of large forest fires, alongside the presence of wind. The study uses climate indices based on the combination of air temperature and precipitation. Forest drought index (FAI) data show that 2007 and 2019 were drier than the 1961–1990 climate period. According to the Lang Precipitation Factor Index (AILang), the periods June–July 2007 and July–October 2019 can be classified as dry. The De Martonne Drought Index (ImDM) shows that July 2007 and October 2019 had the characteristic of areism. These were also the periods when large wildfires were recorded. The results of this study could be used for wildfire risk assessment in protected areas and for fire prevention and suppression planning.